a Pengaruh Lama Fermentasi Dan Konsentrasi Saccharomyces cerevisiae Terhadap Karakteristik Kimia Dan Mikrobiologi Kopi Wine Robusta Di UMKM Oishi - Fatima, Iqfina (Journal Of Agritech Science (JASc), 2024)
Oishi UMKM has one of its superior products, namely wine coffee. The coffee is popular, however, due to the long making process, Oishi MSMEs often cannot fulfill its consumer demands. This study then aims to obtain the best yeast concentration and fermentation time in making Robusta ground wine coffee at Oishi MSMEs to produce a good quality of wine coffee in terms of its chemical, microbiological, and hedonic characteristics, and streamline fermentation time. Moreover, it is also to help Oishi MSMEs in fulfilling its market demand for fermented coffee according to the ground coffee standards. Furthermore, this study was conducted using a two-factor Completely Randomized Design (CRD). The first factor was the fermentation time (2 days, 4 days, and 6 days), while the second factor was the concentration of S.cerevisiae yeast (1%, 2%, and 3%). Each treatment was carried out 3 times. The data were then analyzed using the Analysis of Variance (ANOVA) statistical test, and there were significant differences between treatments, then, we continued with the Duncan Multiple Range Test (DMRT). Based on the results, the fermentation time and yeast concentration have a significant effect on caffeine content, total acid, and hedonic quality. Saccharomyces cerevisiae concentration of 3% and fermentation time of 4 days had the best results, with total plate number results: water content 3.40%, total acid 1.92%, ash content 4.71%, caffeine content 0.932%, total plate number 4.36 Log CFU/g, color taste value 2.67, taste 2.33, aroma 2.67, and overall 3.67.